Network master planning for a global manufacturing company - Heinz, Michael Pierre (Cranfield University, 2006)
Production in global, intra-organisational networks is becoming more common. In this context, the allocation of production quantities to constrained manufacturing capacity is a challenging process. Due to a volatile environment it is argued to be impossible to achieve a ‘clean’ system design with dedicated resources which exactly meets future demand. Thus, recursive ‘Network Master Planning’ (NMP) becomes necessary. The aim of this research is to generate an understanding of the unusual situation of Network Master Planning and enable improvement of NMP practice. The author introduces a specification of requirements that was derived from observation of the real-life NMP planning activity. The relevant literature is presented to focus and position NMP in the field of tactical production planning in the literature and business context. Solution principles, design rules, and an architecture are proposed and combined to a planning methodology. The research is problem-solving in nature and based in management research. The author seeks to develop new understanding by testing hypotheses in practice. Thus, knowledge originates in real world situations. The thesis describes how NMP concepts have been derived in a single-case-study and validated by implementing and testing tool modules incorporating these concepts. The understanding of fundamentals and requirements for NMP, proposed concepts to tackle NMP, and generic findings represent the major contribution to knowledge of this thesis. The core findings of this work are that: • NMP is a series of steps not an isolated task. • Aggregation does not solve the problems of NMP. • Dynamic, multi-objective planning needs human decision makers. • Tool support in NMP means complementing human actions; not replacing them by ‘automatic optimisation’. • It is possible to implement the proposed NMP concepts in a practical procedure. Additionally to building the basis for further work, the findings of this research work are transformed into recommendations particularly for practitioners who are in a similar situation to the case company. The individual points may serve as guidelines to support practitioners working in the field of NMP or restructuring an existing planning system.